Responsibilities with conflicting priorities: a qualitative study of ACT providers' experiences with community treatment orders - Hanne Kilen Stuen; Anne Landheim; Jorun Rugkåsa; Rolf Wynn (BMC, 2018)
Abstract Background Patients with severe mental illness may be subjected to Community Treatment Orders (CTOs) in order to secure that the patients adhere to treatment. Few studies have investigated the use of CTOs within an Assertive Community Treatment (ACT) setting, and little is known about how the tension between the patients' autonomy and the clinicians' responsibility to act in the patients' best interest are resolved in practice. The aim of this study was to explore the service providers' experiences with CTOs within an ACT setting. Methods The study was based on reviews of case files of 15 patients, eight individual qualitative in depth interviews and four focus group interviews with service providers involved in ACT and decisions related to CTOs. A modified grounded theory approach was used to analyze the data. Results The main theme 'responsibility with conflicting priorities' emerged from data analysis (case file reviews, individual interviews and focus group interviews). The balance between coercive approaches and the emphasis on promoting patient autonomy was seen as problematic. The participants saw few alternatives to CTOs as long-term measures to secure ongoing treatment for some of the patients. However, participants perceived the ACT model's comprehensive scope as an opportunity to build rapport with patients and thereby better meet their needs. The team approach, the ACT providers' commitment to establish supportive relationships and the frequent meetings with patients in their home environment were highlighted. The ACT approach gave them insight into patients' everyday lives and, in some cases a greater sense of security when considering whether to take patients off CTOs. Conclusions Many of the participants viewed CTOs as helpful in securing long-term treatment for patients. CTO decision-making was described as challenging and complex and presented the providers with many dilemmas. The ACT approach was considered as helpful in that it afforded comprehensive, patient-centered support and opportunities to build rapport.